Pengaruh Coping Stres terhadap Stres Pengasuhan Guru Muda yang Memiliki Anak Usia Dini - Utami, Nabila Rizki; Formen, Ali (Universitas Muhammadiyah Metro, 2025)
This study aimed to discuss the influence of coping stress and parenting stress of young teachers who have early childhood in Temanggung Regency. This study uses a quantitative approach using two measuring scales; Brife Cope Scale with 28 items and an adapted Parental Stress Scale (PSS) scale of 15 items. Sampling using purposive sampling technique, which is distributed through questionnaires with the specified criteria, at PAUD Institutions in Temanggung, which obtained a total sample of N = 96 young mother teachers who have early childhood. Data analysis was conducted using simple linear regression analysis. From the results of the analysis, showing the significance value of stress coping of 0.005 (p < 0.05) on parenting stress, then Ha is accepted and H0 is rejected, so it can be concluded that stress coping has an influence on the parenting stress of young teachers who have early childhood in Temanggung PAUD units. Stress coping affects the parenting stress of young teachers who have early childhood by 11.7%. Young teacher mothers with high levels of stress coping tend to experience low levels of parenting stress.